Quantitative Easing and Economic Stability: Adaptive Strategies in Indonesia’s New Trinity Framework - Akbar, Dudi Duta; Siregar, Hermanto; Sugema, Iman; Anggraeni, Lukytawati (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates how Quantitative Easing (QE), as an unconventional monetary policy, affects Indonesia's macroeconomic stability amidst increasing global volatility. While QE is intended to stimulate liquidity and economic recovery, its implementation in emerging economies like Indonesia faces structural constraints involving inflation control, exchange rate management, and monetary policy independence. Using 64 quarterly observations from 2007 to 2023, this quantitative research applies nonlinear econometric models including Threshold Vector Autoregression (TVAR), Bayesian Vector Autoregression (BVAR), and Time-Varying Parameter Vector Autoregression (TVP-VAR) to capture regime-dependent and time-varying policy dynamics. The analysis focuses on Indonesia’s macro-financial variables, including policy interest rate, inflation, GDP growth, REER, stock market index (IHSG), and government bonds (SUN). The study adopts the “new monetary trinity” framework, integrating financial stability alongside exchange rate and monetary autonomy. The main findings highlight nonlinear and time-varying relationships among variables: in low-volatility regimes, QE supports inflation control and bond stability, while in high-volatility regimes, it intensifies pressure on GDP and erodes monetary independence. The burden-sharing mechanism between the central bank and the government proves critical in sustaining liquidity and investor confidence. These insights underscore the need for adaptive, well-coordinated fiscal-monetary strategies to enhance resilience in Indonesia and other emerging markets.